Irrigation Network Optimization Using Linear Programming in Wates Irrigation Area, Kediri Regency - Musyaffa Ibrahim Alqowi; Mahendra Andiek Maulana (International Journal of Science and Environment (IJSE), 2026)
Indonesia, as an agrarian country, has a high dependence on the agricultural sector, where the irrigation system plays a crucial role in increasing agricultural productivity. One of the main challenges in irrigation systems is the optimal efficiency of water distribution. This study aims to analyze the condition of the existing irrigation network in the Wates Irrigation Area (Daerah Irigasi/D.I.), Kediri Regency, and to develop an agricultural land optimization strategy based on the availability of irrigation water and a suitable cropping pattern. To enhance the effectiveness of water distribution and allocation in the Wates Irrigation Area, optimization of the existing irrigation network is necessary, considering seasons and water availability. A comparison between the water discharge requirements and the available network capacity is essential. The methodology of this research includes the evaluation of the irrigation network condition, analysis of crop water requirements, and the application of an optimization method using linear programming. The data used comprises climatological data, rainfall, and cropping patterns during the 2014-2024 period. The results indicate that the optimization of irrigation water distribution can increase the efficiency of resource utilization, reduce water wastage, and improve agricultural yields. It is expected that the implementation of this optimization will result in an optimal irrigation network compared to the existing one, thereby increasing farmer welfare and ensuring sustainable food availability. The research findings also provide recommendations for local government and relevant agencies in planning and managing more efficient and optimal irrigation networks in the future. The evaluation in the Wates Irrigation Area identifies that the hydraulic performance of the majority of existing irrigation channels is inadequate due to insufficient capacity and flow velocity exceeding the safe limit, thus requiring a total redesign of the channel dimensions to meet the planned discharge. Concurrently with this infrastructure improvement, agricultural land optimization utilizing a linear programming model with the objective function of maximizing profit and constraints of water availability and land area, tested several alternative cropping patterns; although irrigation water requirements vary (lowest at 914,761 m3/ha in Alternative I), the analysis shows that Alternative I, which begins planting in October I, yields the most significant MK I planting area (876 Ha) and is the most effective cropping pattern as it generates a maximum profit of Rp. 50,465,748,346.